‘Turning the Tide’ - Ann Russell (Applied Phycology, 2024)
‘Turning the Tide’ (2020–present) is the most recent project in my lifelong involvement with seaweed. I write about my use of photography and drawing to capture the fleeting existence of seaweed strewn along the tideline. Spontaneous and free in their creation, my photographs explore the seaweed’s qualities of movement, texture, time and emotion; how it weaves into my own psychology. Seaweed has become a language which writes itself before and within me. ‘Turning the Tide’ redefines our understanding of our own place in the landscape and draws us to seek a wider and deeper connection to the tideline.